2016
DOI: 10.1002/chem.201601062
|View full text |Cite
|
Sign up to set email alerts
|

Wolves in Sheep's Clothing: μ‐Oxo‐Diiron Corroles Revisited

Abstract: For well over 20 years, μ-oxo-diiron corroles, first reported by Vogel and co-workers in the form of μ-oxo-bis[(octaethylcorrolato)iron] (Mössbauer δ 0.02 mm s(-1) , ΔEQ 2.35 mm s(-1) ), have been thought of as comprising a pair antiferromagnetically coupled low-spin Fe(IV) centers. The remarkable stability of these complexes, which can be handled at room temperature and crystallographically analyzed, present a sharp contrast to the fleeting nature of enzymatic, iron(IV)-oxo intermediates. An array of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Over a long series of studies, we have shown that Soret maxima of innocent metallotriarylcorroles, such as CrO and MoO corroles, TcO and ReO corroles, RuN and OsN corroles, and Au corroles, are insensitive to the meso -aryl para substituent X. In contrast, the Soret maxima of noninnocent metallotriarylcorroles, of which Mn, Fe, Cu, and certain Pt corroles provide salient examples, undergo marked red shifts with increasing electron-donating character of the substituent X. As shown in Figure and Table , we encounter both behaviors in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Over a long series of studies, we have shown that Soret maxima of innocent metallotriarylcorroles, such as CrO and MoO corroles, TcO and ReO corroles, RuN and OsN corroles, and Au corroles, are insensitive to the meso -aryl para substituent X. In contrast, the Soret maxima of noninnocent metallotriarylcorroles, of which Mn, Fe, Cu, and certain Pt corroles provide salient examples, undergo marked red shifts with increasing electron-donating character of the substituent X. As shown in Figure and Table , we encounter both behaviors in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, metallocorroles have provided many examples of well-characterized noninnocent systems. [19][20][21][22] Key examples include MnCl, 23 FeCl, [9][10][11][12][13][14][15] FeNO, [24][25][26][27] Fe 2 (μ-O), 28 Copy 29 /DMSO 30 ( py = pyridine), Co-PPh 3 , 31 and Cu [32][33][34][35][36][37][38][39][40] corrole derivatives. It is worth noting that all these involve first-row transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Such strong saddling is not observed for gold corroles owing to an energy mismatch between the Au 5dnormalx2-normaly2 orbital and the corrole a 2u HOMO; Au corroles thus are best viewed as Au III ‐corrole 3− . Recently, we showed that FeNO corroles and μ ‐oxo di‐iron corroles provide additional examples of cryptic noninnocence, that is, of diamagnetic metallocorroles that are nonetheless best thought of as corrole .2− radical derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] No analogous spectral shifts are observed for innocent metallotriarylcorroles. [10,[15][16][17][18] This empirical correlation has provens or eliable that we used it in ap redictive manner to identify new families of noninnocent complexes,n otably FeNO [11] corroles and m-oxodi-iron [12] corroles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation